Photonic nanojet mediated Raman enhancement: Vertical Raman mapping and simple ray matrix analysis. (21st November 2019) - Gašparić, Vlatko; Taccheo, Stefano; Gebavi, Hrvoje; Ristić, Davor; Ivanda, Mile
Abstract: A new method for enhancing the Raman scattering signal has emerged recently, based on dielectric enhancement. Especially promising is the dielectric method based on microspheres and photonic nanojet. In this paper, geometrical aspects and the influence of the incident beam parameters on Raman enhancement by silica microspheres were systematically investigated in three steps: by characterizing the incident beam using knife‐edge method, performing horizontal and vertical Raman mapping imaging, and analyzing the results using ray transfer matrix analysis. Maps show a distinct enhancement (hotspot) area caused by the microsphere photonic nanojet and lens effect compared to a plain silicon substrate. Enhancement value on maps was the highest (5.7×) for 0.50 numerical aperture objective, when the incident beam size matched the microsphere diameter, and the focus of the incident beam was below the top of the sphere, so that the output beam focus was at the microsphere–substrate contact area. This geometrical configuration was confirmed as ideal by performing simple ray transfer matrix analysis. The ideal ranges of incident and output beam parameters match with the measured hotspot area. This three‐step process and the usage of vertical Raman mapping have been, for the best of our knowledge, performed for the first time in such configuration. This research introduces a new way of investigating microsphere‐assisted Raman enhancement, offers different approach to microsphere optics research, and improves current knowledge of the influence of the incident beam on the enhancement. Abstract : By measuring vertical Raman mapping images, Raman enhancement area of the silicon substrate signal can be seen, which is caused by the microsphere on top. The highest enhancement (5.7×) is gained using 0.50 NA objective, when the incident beam focus is 9 μm below the top of the sphere. Experimental data are explained using ray matrix analysis.